HUBUNGAN KECANDUAN SMARTPHONE DENGAN KECENDERUNGAN PERILAKU PHUBBING PADA REMAJA DI SMAN 34 JAKARTA SELATAN - Eduardo Taufik (2020)
Smartphone was one of the most popular technologies in Indonesia that was most widely used to access the internet. About 70% of the most internet users in Indonesia were mostly recorded as adolescents, 13-18 years out of 70%. Teenagers were very susceptible to the adverse effects of the development of smartphone technology such as the emergence of smartphone addiction and phubbing behavior. This research method uses a cross-sectional analytic observational research design. The subjects of this study were students of SMAN 34 South Jakarta consisting of 100 students. The results of this study found that the p-value <0.005 and the correlation coefficient value (c) = 0.569. This means that there was a significant relationship between smartphone addiction and phubbing behavior in adolescents at SMAN 34 South Jakarta.. This research also shows that most of the teenagers of SMAN 34 South Jakarta were in the category of moderate smartphone addiction with moderate phubbing behavior.